Synthesis of an Azido-Substituted 8-Membered Ring Laddersiloxane and Its Application in Catalysis - Yujia Liu; Niyaz Yagafarov; Koki Shimamura; Nobuhiro Takeda; Masafumi Unno; Armelle Ouali (Molecules)
A first syn-type tricyclic 8-8-8 (three fused-8-membered ring) laddersiloxane functionalized with four azido groups was successfully synthesized through efficient and highly selective hydrosilylation and nucleophilic substitution, achieving an excellent overall yield. The starting material, a tetravinyl-substituted 8-8-8 laddersiloxane, was prepared via a straightforward and scalable method. The obtained azido-functionalized ladder compound, fully characterized, constitutes a versatile building block for hybrid materials. Reacting this compound with 2-ethynylpyridine via click chemistry yielded a multidentate ligand containing four 2-triazole-pyridyl moieties. This N,N-bidentate ligand was subsequently employed in copper-catalyzed alcohol oxidative dehydrogenation reactions, demonstrating its potential in catalysis.